2002
DOI: 10.1046/j.1365-2958.2002.03226.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposition of the Ll.LtrB group II intron proceeds predominantly via reverse splicing into DNA targets

Abstract: SummaryCatalytic group II introns are mobile retroelements that invade cognate intronless genes via retrohoming, where the introns reverse splice into double-stranded DNA (dsDNA) targets. They can also retrotranspose to ectopic sites at low frequencies. Whereas our previous studies with a bacterial intron, Ll.LtrB, supported frequent use of RNA targets during retrotransposition, recent experiments with a retrotransposition indicator gene indicate that DNA, rather than RNA, is a prominent target, with both dsDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
94
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 60 publications
2
94
0
Order By: Relevance
“…To the best of our knowledge, such a mechanism has not been identified or proposed previously for DNA transposons. However, homology between the MGE RNA and the integration region in the host genome is exploited during group II intron retrohoming (71,72), suggesting that RNA-guided target recognition evolved more than once in MGE evolution. Many questions remain regarding the functioning of the CRISPRCas in Tn7-like transposons, including the possibility of direct interaction between the CRISPR effector complexes and TnsD(TniQ), TnsABC, or other transposon-encoded accessory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, such a mechanism has not been identified or proposed previously for DNA transposons. However, homology between the MGE RNA and the integration region in the host genome is exploited during group II intron retrohoming (71,72), suggesting that RNA-guided target recognition evolved more than once in MGE evolution. Many questions remain regarding the functioning of the CRISPRCas in Tn7-like transposons, including the possibility of direct interaction between the CRISPR effector complexes and TnsD(TniQ), TnsABC, or other transposon-encoded accessory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The most probable source is ssDNA at the DNA replication fork because this ssDNA is the substrate for other group II introns that lack endonuclease domains (20,21,32). In this pathway, the intron reverse splices into either ssDNA or dsDNA at the replication fork and then uses nascent DNA of the leading or lagging strands to prime reverse transcription of the intron.…”
Section: Discussionmentioning
confidence: 99%
“…Other bacterial introns also lack endonuclease domains (e.g., bacterial classes A, D, and E), but introns of these classes are nevertheless mobile (18,19). The mechanism has been shown to involve the DNA replication fork, with the intron reverse splicing into either ssDNA or dsDNA and the primer being provided by either the leading or lagging strand (20,21).To address how bacterial class C introns insert at terminator motifs, we have investigated the B.h.I1 intron of Bacillus halodurans because it initially appeared to have a degree of sitespecificity, which would facilitate characterization. There are five B.h.I1 intron copies in the B. halodurans genome (Ͼ99.8% identity), with four located at analogous sites after the terminators of ribosomal RNA (rrn) operons B, D, F, and G (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because these retroelements rely on either DNA replication forks (17) or damaged DNA, including nicks, as target sites (18), acquisition of an endonuclease domain would likely have enhanced the efficiency and range of such elements. Remarkably, the study by Gladyshev and Arkhipova (7) revealed that functional copies of nuclease-deficient PLEs in species from protist, fungal, and plant clades are effectively single-copy genes, unlike nucleasecontaining retrotransposons.…”
mentioning
confidence: 99%